Relationship of neutrophil-to-lymphocyte and platelet-to-lymphocyte ratio with visual acuity after surgical repair of open globe injury - Mohamed Noriega, Karim; Treviño Herrera, Alan Bる; Mohamed Noriega, Jibran; Velasco Sepúlveda, Braulio H.; Martínez Pacheco, Víctor Alejandro; Guevara Villarreal, Dante A.; Rodríguez Medellín, Delia L.; Sepúlveda Salinas, Anna G.; Villarreal Mendez, Gerardo; González Cortés, Jesús H.; Elizondo Omaña, Rodrigo Enrique; Guzmán López, Santos; et al. (Frontiers Media, 2021)
Background: Male EBP disorder with neurologic defects (MEND) syndrome is an　X‐linked disease caused by hypomorphic mutations in the EBP (emopamil‐binding　protein) gene. Modifier genes may explain the clinical variability among individuals　who share a primary mutation. Methods: We studied four males (Patient 1 to Patient 4) exhibiting a descending　degree of phenotypic severity from a family with MEND syndrome. To identify candidate modifier genes that explain the phenotypic variability, variants of homeostasis　cholesterol genes identified by whole‐exome sequencing (WES) were ranked according to the predicted magnitude of their effect through an in‐house scoring system. Results: Twenty‐seven from 105 missense variants found in 45 genes of the four　exomes were considered significant (−5 to −9 scores). We found a direct genotype–phenotype association based on the differential accumulation of potentially functional gene variants among males. Patient 1 exhibited 17 variants, both Patients 2 and　3 exhibited nine variants, and Patient 4 exhibited only five variants. Conclusion: We conclude that APOA5 (rs3135506), ABCA1 (rs9282541), and　APOB (rs679899 and rs12714225) are the most relevant candidate modifier genes　in this family. Relative accumulation of the deficiencies associated with variants of　these genes along with other lesser deficiencies in other genes appears to explain the　variable expressivity in MEND syndrome.